2020
DOI: 10.3389/fendo.2020.00477
|View full text |Cite
|
Sign up to set email alerts
|

Intracystic Hemorrhage and Its Management During Ultrasound-Guided Percutaneous Microwave Ablation for Cystic Thyroid Nodules

Abstract: Background: Intracystic hemorrhage can present occasionally during ultrasound-guided percutaneous microwave ablation (PMWA) for cystic thyroid nodules. It can affect treatment outcome, can lead to ablation failure, and even conversion to open surgery. We aim to avoid such cases in the future by exploring their causes and management. Methods: From March 2017 to December 2019, we retrospectively studied 87 cystic thyroid nodules in 59 patients who underwent PMWA in the First Hospital of Jilin University. All pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…Not surprisingly, our results showed that the incidence of intracystic hemorrhage in Group B was 40%. Compared with previous studies (4,8,15,18), the probability of intracystic hemorrhage was extremely high. The main reasons for our finding were as follows: First, these nodules with intracystic hemorrhage were large in mean volume (V=19.5 ml) and high in capsule wall tension.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Not surprisingly, our results showed that the incidence of intracystic hemorrhage in Group B was 40%. Compared with previous studies (4,8,15,18), the probability of intracystic hemorrhage was extremely high. The main reasons for our finding were as follows: First, these nodules with intracystic hemorrhage were large in mean volume (V=19.5 ml) and high in capsule wall tension.…”
Section: Discussioncontrasting
confidence: 74%
“…Sometimes enlargement was visible to the naked eye, and even in some special cases, bleeding points and blood flow could be seen. Bleeding was confined to the cysts and did not affect other tissues (15). Once this happened, the puncture point was compressed for 3-5 min to staunch bleeding.…”
Section: Mwa Proceduresmentioning
confidence: 99%
“…Further, US-guided percutaneous thermal ablation can lead to intracystic hemorrhage when used in the treatment and management of cystic thyroid nodules, which significantly prolongs ablation time and can negatively affect treatment outcome. Dong et al (34) reported an incidence of 10.3% (9/87 cysts) of intracystic hemorrhage, and larger cystic thyroid nodules were more likely to develop intracystic bleeding during US-guided percutaneous MWA. The efficacy of US-guided percutaneous LA is affected by thyroid nodule morphology (54).…”
Section: Limitations Of Ultrasound-guided Thermal Ablation Of Benign Thyroid Nodulesmentioning
confidence: 99%
“…Twelve months after treatment of nodules of metastatic PTC lymph nodes using single-fiber LA, mean baseline volumes reduced from 0.29 ± 0.12 to 0.03 ± 0.03 mL, and the mean VRR was 90.3 ± 7.6%. These findings indicate that thermal ablation, such as LA performed under US guidance, is promising and favorable for the treatment and management of metastatic lymph nodes in PTC, with appropriate ablation modes (34). Han et al ( 70) evaluated the safety and efficacy of percutaneous US-guided microwave ablation for 98 cervical metastatic lymph nodes in patients with PTC.…”
Section: Progress In the Clinical Applications Of Ultrasound-guided Thermal Ablation In Malignant Thyroid Nodulesmentioning
confidence: 99%
See 1 more Smart Citation